2010
DOI: 10.1074/jbc.m110.102988
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Murine Mitochondria-associated Neutral Sphingomyelinase (MA-nSMase), the Mammalian Sphingomyelin Phosphodiesterase 5

Abstract: Sphingolipids play important roles in regulating cellular responses. Although mitochondria contain sphingolipids, direct regulation of their levels in mitochondria or mitochondria-associated membranes is mostly unclear. Neutral SMase (N-SMase) isoforms, which catalyze hydrolysis of sphingomyelin (SM) to ceramide and phosphocholine, have been found in the mitochondria of yeast and zebrafish, yet their existence in mammalian mitochondria remains unknown. Here, we have identified and cloned a cDNA based on nSMase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 45 publications
3
115
0
Order By: Relevance
“…The hydrolysis of sphingomyelin (SM) 2 is a major pathway for ceramide production, and this reaction is catalyzed by the sphingomyelinases (SMases). Currently, six different SMases have been identified and grouped based upon their catalytic pH optima, including an acid SMase, an alkaline SMase and four neutral SMases (N-SMases) (5)(6)(7)(8). Activation of N-SMases has been implicated in various biological responses, such as growth arrest, inflammation and aging (9,10).…”
mentioning
confidence: 99%
“…The hydrolysis of sphingomyelin (SM) 2 is a major pathway for ceramide production, and this reaction is catalyzed by the sphingomyelinases (SMases). Currently, six different SMases have been identified and grouped based upon their catalytic pH optima, including an acid SMase, an alkaline SMase and four neutral SMases (N-SMases) (5)(6)(7)(8). Activation of N-SMases has been implicated in various biological responses, such as growth arrest, inflammation and aging (9,10).…”
mentioning
confidence: 99%
“…On the basis of molecular cloning and confocal microscopy data, this activity was ascribed to mitochondria (El Bawab et al 2000); and it was demonstrated in purified mitochondria (Bionda et al 2004). A recent report suggests that ceramide could be also generated by novel mitochondrial neutral SMase hydrolyzing SM (Wu et al 2010). Given the existence and the likelihood for each one of these various pathways to occur in the mitochondria, continued research efforts are required to better understand the mechanisms of mitochondrial ceramide generation and utilization, along with their influence on mitochondrial functions.…”
Section: Hypothetical Model Of Ceramide Trafficking In Oocytesmentioning
confidence: 99%
“…Mitochondria are important intracellular compartments of sphingolipid metabolism (Novgorodov & Gudz 2009), and several sphingolipid-metabolizing enzymes were found to be associated with mitochondria; so far the list includes neutral ceramidase (El Bawab et al 2000), novel neutral SMase (Wu et al 2010, Clarke et al 2011, and (dihydro) CerS, a key enzyme in de novo ceramide synthesis (Bionda et al 2004, Yu et al 2007. The existence of these compartment-specific pathways clearly suggests high specialization of these pathways, which in turn suggests specific mechanisms of Ceramide and mitochondrial function in aging oocytes regulation and, equally as likely, distinct functions and mechanisms of action of their lipid products.…”
Section: Ceramide and Oocyte Agingmentioning
confidence: 99%
“…Furthermore, it appears that oxidative stress could induce nSMase2 trafficking to the plasma membrane, whereas antioxidant (glutathione) directed its translocation to the perinuclear region (Levy et al, 2006). MA-nSMase is found within the mitochondria and associated membranes (Wu et al, 2010). The physiological role of neutral SMase isoforms may be dictated by their immediate environment in the specific intracellular compartment.…”
Section: Neutral Smasementioning
confidence: 99%